2019
DOI: 10.1002/adma.201901124
|View full text |Cite
|
Sign up to set email alerts
|

Guided Assembly of Microporous/Mesoporous Manganese Phosphates by Bifunctional Organophosphonic Acid Etching and Templating

Abstract: Manganese (Mn)‐based compounds are important materials for both energy conversion and energy storage. Unfortunately, it has been a significant challenge to develop highly ordered microporous/mesoporous structures for them to provide more active sites for these applications. In order to do so using the soft‐templating method, three conditions have to be met, namely, a strong interaction between the inorganic precursor and the organic templates; eliminating the formation of bulk manganese phosphate; and the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…[ 18,27–29 ] In order to keep the catalysts active, introducing new catalytic active sites is one of the most attractive strategies. [ 22,30–37 ] The incorporation of phosphorus (P) into metal nanoparticles (metal phosphide) can stabilize the metal state and modify the electronic state of metal species, which is beneficial to the catalytic performance and selectivity of hydrogenation. [ 34,35,37 ] In addition to the active sites, the support also plays an important role in catalytic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18,27–29 ] In order to keep the catalysts active, introducing new catalytic active sites is one of the most attractive strategies. [ 22,30–37 ] The incorporation of phosphorus (P) into metal nanoparticles (metal phosphide) can stabilize the metal state and modify the electronic state of metal species, which is beneficial to the catalytic performance and selectivity of hydrogenation. [ 34,35,37 ] In addition to the active sites, the support also plays an important role in catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] As a widely used and excellent catalyst in various electrocatalytic reaction, manganese phosphate displays high electrical conductivity and catalytic activity due to the stabilization of the active sites by the phosphate framework and better electron transfer during catalytic reactions. [ 36 ] Combining the advantages of metal phosphides and phosphates to construct SMSI may have great potential to achieve highly active and stable catalyst for efficient hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…NOSPC and Mn SA –N–C O,S exhibited a similar ultrathin nanosheet with a smooth surface (Figures b and S3), and no obvious aggregation of Mn nanoparticles could be observed in the high-resolution TEM (HR-TEM) image of Mn SA –N–C O,S (Figure c). Moreover, Mn SA –N–C O,S exhibited predominantly microporous structures (Figure S4), and a remarkable specific surface area (310.19 m 2 /g) and pore volume (0.14 cm 3 /g), providing abundant active sites and facilitating mass transfer to ultimately enhance its catalytic activity . The energy dispersion spectroscopy (EDS) images under the TEM model (Figure d) revealed that C, N, O, S, and Mn atoms are uniformly distributed in Mn SA –N–C O,S .…”
Section: Resultsmentioning
confidence: 99%
“…The transition metal (Mn, Fe, and Vn) compounds are highly redox‐active, and the pharmacokinetic researches proved that natural Mn‐SOD is much better than Cu/Zn‐SOD and Fe‐SOD. [ 64,65 ] MnO 2 NPs are the most extensively investigated biocatalytic nanostructures, which can catalyze the H 2 O 2 into O 2 and H 2 O. Owing to the co‐existence of Mn 2+ and Mn 3+ , Mn 3 O 4 NPs are capable of eliminating O 2 •− by the dismutation of O 2 •− into O 2 and H 2 O 2 and catalyze the elimination of H 2 O 2 . The modeled Fenton‐like reaction between iron‐based NPs and H 2 O 2 may generate ROS.…”
Section: Ros Scavenging Mechanisms and Evaluation Methodsmentioning
confidence: 99%